SiC Foams Decorated with SnO2 Nanostructures for Room Temperature Gas Sensing. Issue 5 (1st August 2014) - Karakuscu, Aylin; Ponzoni, Andrea; Comini, Elisabetta; Sberveglieri, Giorgio; Vakifahmetoglu, Cekdar
<x xml:space="preserve">Abstract</x> Cell walls of the commercial silicon carbide (SiC)‐based foams were decorated by one‐dimensional tin dioxide (SnO2) nanostructures. Thermal evaporation of SnO2 powder with the assistance of a Au catalyst in inert atmosphere caused the formation of SnO2 nanobelts on the pore surfaces. The room temperature (RT) ammonia (NH3) and nitrogen dioxide (NO2) gas sensing behaviors were investigated systematically in both dry and humid air atmosphere with/without UV activation. The results were compared to those for bare SnO2 and SiC. It was shown that SiC/SnO2 composite was efficient to detect low concentration of NH3 (10–50 ppm) and NO2 (1–5 ppm) under humid air and UV activation at RT.